The Effact of waste frying oil biodiesel based mud on rubber components - 346253 Nurfadzilah Reman; Azmi Kamis, supervisor (Skudai : Universiti Teknologi Malaysia, 2010)
Project Paper (Sarjana Muda Kejuruteraan Petroleum) - Universiti Teknologi Malaysia, 2010